Deltas in the Anthropocene 2019
DOI: 10.1007/978-3-030-23517-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial Sediment Supply and Relative Sea-Level Rise

Abstract: The world’s deltas are facing a sustainability crisis, with many at high risk of being ‘drowned’ as a result of relative sea-level rise. The only factor that can potentially offset relative sea-level rise is the deposition of fluvial sediment on the surface of deltas. As a result, an understanding of trends in fluvial sediment supply to deltas is critical for understanding the potential of different deltas to adapt to the threat of drowning. Here trends of sediment supply to three of the world’s deltas (the Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The Volta River Delta is the sanctuary for about 80% of migratory birds that transit in Ghana's wet semi-equatorial and dry equatorial climatic zones [25,28]. The sediment of the Volta River Delta is mostly sand with a median grain size of 0.6 mm [28,29]. The anthropogenic interventions of damming and irrigation, as well as the associated evaporation, alter the variation of river discharge and sediment load, further affecting the delta morphology [30].…”
Section: The Volta Rivermentioning
confidence: 99%
“…The Volta River Delta is the sanctuary for about 80% of migratory birds that transit in Ghana's wet semi-equatorial and dry equatorial climatic zones [25,28]. The sediment of the Volta River Delta is mostly sand with a median grain size of 0.6 mm [28,29]. The anthropogenic interventions of damming and irrigation, as well as the associated evaporation, alter the variation of river discharge and sediment load, further affecting the delta morphology [30].…”
Section: The Volta Rivermentioning
confidence: 99%
“…The rate of accretion in what is today a highly modified GBM delta depends on how much incoming fluvial and/or marine sediment flux is retained on the delta surface. The physical sustainability of the delta depends on the future rate of fluvial sediment supply (Darby et al, 2018(Darby et al, , 2020 and its dispersion processes (Wilson et al, 2017) through the channel networks that intersect the delta surface. Recently, Dunn et al (2019) showed that the supply of fluvial sediment to the GBM delta is likely to decline significantly in the future due to anthropogenic changes in the upstream catchment.…”
Section: Introductionmentioning
confidence: 99%
“…The Bengal Delta, also known as the Ganges-Brahmaputra-Meghna Delta, is the second largest delta in the world (Darby et al, 2020). It covers more than 100 000 km 2 and has been continuously gaining land by 17 km 2 year −1 over the last five decades (Sarker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%